Policing in a relational state: the case of sorcery accusation-related violence in Papua New Guinea. (28th May 2022) - Forsyth, Miranda
ABSTRACT: Sorcery accusation-related violence raises many profound policing challenges, especially in countries where police forces find themselves outnumbered and outgunned by mobs of perpetrators. Drawing on empirical evidence from a multi-year study into this phenomenon in Papua New Guinea reveals the ways in which police officer's relationality both enables and impedes the provision of policing and security in such contexts. Using this as a case study of common concerns across multiple bodies of literature about the relationship between formality and informality and dilemmas of working with a plurality of regulatory actors, the article draws upon complexity science to develop a number of conceptual tools. These include the suggestion of conceptualising policing systems as complex adaptive systems, with police as adaptive agents with multiple relationships constituting shifting identities, and the importance of integrating multiple perspectives. This leads to the development of the notion of the police acting within a relational state that is entwined with a more familiar bureaucratic state.